Entrepreneurial intentions and high-status seeking in career expectations: a portrait of talents in emerging countries. Issue 11 (17th June 2022) - Orlando, Beatrice; Tortora, Debora; Riso, Teresa; Di Gregorio, Angelo; Del Giudice, Manlio
Abstract: Nowadays organizations are increasingly engaged in talent management, because it allows firms to grow rapidly by leveraging on human capital. Most antecedent studies focused on expectations and motivations of talents living in developed countries. Though, a little is known about career expectations of talents in emerging economies, and whether they diverge from those of developed countries or not. However, this information might be of use for several motives. First, emerging countries have a high growth rate. Second, these talents may be effectively harnessed from domestic and non-domestic firms, depending on whether their expectations are met or not. Consistently, this study aims at exploring the career expectations of individuals in emerging countries, by capturing the heterogeneity of expectations between emerging and developed countries due to cultural, politic, economic, and religious differences. As a matter of fact, emerging countries are frequently characterized by low levels of both income and employment, differently from many developed countries. For such motives and because of the absence of valid employment alternatives, talents might be more willing to engage in entrepreneurial initiatives rather than attempting to be employed in an organization. Thus, the primary intent of this explorative study is to understand what are the factors that affect career expectations of talents in emerging countries. Consistently, a cross-sectional principal component analysis (PCA) was used for hypotheses testing. The sample refers to a set of African countries, based on data availability for 2019. Data used for the analysis are drawn from the Global Entrepreneurship Monitor (GEM) and they refer to individual entrepreneurial behaviours and attitudes. Notably, findings show that career expectations of talents are driven by motivation and opportunity, especially in the male groups. However, the study also originally shows that the need for achievement and the willingness to stand out are the main drivers of talents' expectations. In a nutshell, talents may prefer independence over the employment status. Implications of the findings, at a business level, suggest that companies in emerging markets should revisit their talent management strategy in order to avoid the loss of many talented employees. As instance, they should grant more independence, raise the income, and favour internal and female entrepreneurship. Thereby, the original findings of the study contribute both theoretically and practically to the research domain by specifying that career needs of talented people vary according to context and time.